A UNEB e a promoção do desenvolvimento local e regional: o caso dos cursos de Pós-graduação Stricto Sensu: uma análise de 2002 a 2013 - SANTOS, Luiz Carlos dos (2015)
This study had as goal of analyzing, from courses projects, what sensu post-graduation offered by Universidade Estadual da Bahia (UNEB), from 2002-2013, have relationship to doctorate and mastership courses in regional and local development in Brazil in a sustainable, economical and social perspective by having the Municipal Human Development Index (MDI) as a variable. Such a research has been based upon a case study, in an exploratory, descriptive and qualitative way by including the courses, goals, concentration area, kind of research and people linked to that. Thinking the regional and local development is in fact to recognize the culture, environment, knowledge, technologies, identities, economical relations, social organizations, historical and peculiarities differences, that is, recognizing the diversities and respecting them in order to develop them, nevertheless, the global context should always be the parameter. The development is only possible with Education process within which the universities as well as their teaching are really too fundamental and specially the Public ones are responsible for dealing with critical learning by letting more autonomy for their students, due to that, there is an improvement in society with such a teaching, research and extension. In face of much information, another variable “weight” which has been linked to Spearman’s and Kendall’s coefficient has been analyzed and has been checked the link to IES post- graduation, study object, the development and its terminologies. Due to the ones linked to the sensu post-graduation and development, through interviews, it has been concluded that UNEB has contributed for the regional and local development in State. It has been made too many recommendations, however, it is crucial to call attention to the need of reviewing post-graduation policy in order to include the whole university as well as implement research policy, science, technology and innovation in order to consolidate a deeper development in academic environment.